(3EUdGM GdNdd aj cJGH GdLeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi de jJNP hdjkG hdG XgjQG GdcJGH GdChdi bGd CHh GdbGSe GdRLGLi GdfMhi QMeg Gddg CbSGe GdcdGe KdGKI GSe haYd hMQa s
(3BNQgG (B:s
(3BNQ eG XgQ efgG aeG HQMJ MJi eUfa Gddjd hGfbVi hCYLdgG OGYi GdUHGM GdedeM s
(3HgG GKGQ JbWjYs
(3HgG fXGe GdJYbjHIs
(3COJ GdQWhHI Edi WeS HYV GdcdeGJs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs